1998
DOI: 10.1002/(sici)1097-0215(19980209)75:4<654::aid-ijc26>3.3.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol and fibulin‐1 inhibit motility of human ovarian‐ and breast‐cancer cells induced by fibronectin

Abstract: Ovarian-cancer cells are characterized by their ability to invade freely the peritoneal cavity. Estradiol stimulates the proliferation of estrogen-receptor(ER)-positive ovariancancer cells, as well as expression of fibulin-1, a fibronectinbinding extracellular matrix protein. Using a modified Boydenchamber assay, we have evaluated the respective roles of estradiol and fibulin-1 on cell motility, one of the earlier steps of tumor invasion. The effect of estradiol was examined on the random and directional migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 0 publications
5
32
0
Order By: Relevance
“…More recent studies have demonstrated that estradiol significantly reduces invasiveness and that this inhibition is reversed by antiestrogens [83][84][85][86][87]. This conclusion was noted in several ER-positive cancer cell lines established from breast [83] or ovary [85], and in different ER-negative cancer cells constitutively expressing ER after stable transfection [45,84,87]. Similar results were also obtained on the migration of normal cells from vascular smooth muscle [86].…”
Section: Estrogens Inhibit Invasion Via Ere-regulated Genessupporting
confidence: 65%
See 1 more Smart Citation
“…More recent studies have demonstrated that estradiol significantly reduces invasiveness and that this inhibition is reversed by antiestrogens [83][84][85][86][87]. This conclusion was noted in several ER-positive cancer cell lines established from breast [83] or ovary [85], and in different ER-negative cancer cells constitutively expressing ER after stable transfection [45,84,87]. Similar results were also obtained on the migration of normal cells from vascular smooth muscle [86].…”
Section: Estrogens Inhibit Invasion Via Ere-regulated Genessupporting
confidence: 65%
“…The initial studies indicated that the invasiveness of MCF7 breast cancer cells was increased by antiestrogens [81,82]. More recent studies have demonstrated that estradiol significantly reduces invasiveness and that this inhibition is reversed by antiestrogens [83][84][85][86][87]. This conclusion was noted in several ER-positive cancer cell lines established from breast [83] or ovary [85], and in different ER-negative cancer cells constitutively expressing ER after stable transfection [45,84,87].…”
Section: Estrogens Inhibit Invasion Via Ere-regulated Genesmentioning
confidence: 96%
“…The biologic functions of these transcripts appear to be variant-specific (Moll et al, 2002). Fbln-1 can self-associate and bind to ECM proteins, including fibronectin, laminin and nidogen, and to the coagulation protein fibrinogen (Hayashido et al, 1998). Fbln-1 is found in basement membranes and in loose connective tissue associated with matrix fibres (Roark et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that ®bulin-1 protein expression is increased in human ovarian epithelial cancers as compared to normal and benign tumors and that epithelial ovarian cells expressed ®bulin-1 mRNA in vivo . The ability of ®bulin-1 to bind extracellular matrix proteins such as ®bronectin and laminin and its localization at sites of epithelial mesenchymal transition suggest a role in cell attachment and motility (Hayashido et al, 1998;Pan et al, 1993;Balbona et al, 1992;Aspberg et al, 1999;Roark et al, 1995).…”
Section: Introductionmentioning
confidence: 99%